"VERHOVINO, YOU ARE OUR LIGHT…" (THOUSAND AUTOGRAPHS, AMONG THEM QUITE A BIT UNIQUE, IN ONE HANDWRITTEN BOOK) - Pogrebennyk , F. G. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the question is the autographs of prominent figures of science and culture, collected in the «Memory book of tourists which were the guest of in the house» of Teofily Kisilevsky – manager of folk school in Gab'e-Iltsi on Kosiv region (in 1904-1932).